Divergent Memory B Cell Responses in a Mixed Infant Pneumococcal Conjugate Vaccine Schedule - Trück, J; Mitchell, R; Jawad, S; Clutterbuck, E; Snape, M; Kelly, D; Voysey, M; Pollard, A (Wolters Kluwer Health, Inc., 2016)
BACKGROUND: Vaccine-induced immunity against pneumococcal infection relies on the generation of high concentrations of antibody and B-cell memory. Both the 10- and the 13-valent pneumococcal conjugate vaccines (PCV-10 and PCV-13) effectively reduce disease caused by vaccine serotypes. It is unknown whether the generation of B-cell memory requires several doses of the same vaccine or whether different PCVs are interchangeable. METHODS: Children in the UK (n=178) who had previously received PCV-13 at 2 and 4 months were randomized 1:1 to receive a PCV-13 or PCV-10 booster at age 12 months. Peripheral blood memory B cells (BMEM) were quantified before and at 1 and 12 months following vaccination using a cultured ELISpot assay for pneumococcal serotypes 1, 3, 4, 9V, 14, 19A and diphtheria and tetanus toxoid. Correlations between BMEM frequencies and simultaneously measured antibody (IgG and OPA) was also assessed. RESULTS: A significant rise in post-booster BMEM frequency was seen for 5 out of six serotypes in the PCV-13 group and none in the PCV-10 group. In the PCV-13 group, there was a particularly large increase in serotype 3-specific BMEM associated with only a small increase in antibody. Post-booster BMEM responses correlated positively with antibody, but correlations between pre-booster BMEM and subsequent BMEM and antibody responses were inconsistent. CONCLUSIONS: Following priming with PCV-13 in early infancy, a booster dose of PCV-10 does not induce detectable peripheral blood BMEM responses but a PCV-13 booster does induce robust responses. Booster responses to pneumococcal conjugate vaccines may be dependent on homologous carrier protein priming.